Sugar content in breakfast cereals and yogurts: the Portuguese market baseline in order to design and promote healthy eating - Vargues, Andreia Lopes (2019)
Introduction Scientific studies have related excessive sugar intake to chronic diseases, such as diabetes and obesity, leading several European countries, namely Nordic, United Kingdom and Ireland, to the development of initiatives towards public health. Portugal has defined an integrated strategy that encourages healthy eating (EIPAS) and aims for a major reduction of sugar intake. To accomplish this, monitoring sugar content in food is required. Objectives Evaluate and compare sugar content in breakfast cereals and in solid and liquid yogurts, in Portugal and Ireland, focusing those near and below the goal established by EIPAS, for 2021.